PENGARUH PERKUATAN TIANG TERHADAP STABILITAS TIMBUNAN DIATAS TANAH LUNAK MENGGUNAKAN METODE ELEMEN HINGGA - Bambang Setiawan; Raden Harya Dananjaya H.I.; Muhammad Fathurrahman (Prodi Teknik Sipil FT Universitas Sebelas Maret, 2020)
Pile strength is widely used as a solution to the problem of road pavement on soft soil, because it can reduce vertical displacement due to the load on it and increase the safety factor value. This research analyses the vertical displacement, safety factor, effective stress and bearing capacity of the embankment on soft soil using the finite element method so the results can approach the original conditions in the field. The pile variations used are pile size variations 20x20 cm2; 25x25 cm2; and 30x30 cm2 with a square shape, variations in the distance between the piles 1,60 m; 1,80 m; 2,00 m; and 2,20 m, the depth variations 15,00 m; and 20,00 m. Loading uses truck loads based on RSNI T-14-2004 and the road classification is artery IA. The results of the analysis show that pile strength with a size 20x20 cm2, the distance between pile is 1,60 m and the depth of the piles 20 m can reduce the vertical displacement by 71,31% and increase the safety factor by 123,25%.